O papel das tecnologias digitais em disciplinas de álgebra linear a distância: possibilidades, limites e desafios - Chiari, Aparecida [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The objective of this research is to understand the role of digital technologies (DT) in educational processes associated with Linear Algebra in four distance teacher education in mathematics courses linked to the Open University of Brazil (UAB), in the context of its Virtual Learning Environments (VLE). It is a qualitative study. The study and the analysis are guided by theoretical perspectives related to modes of description in Linear Algebra, the notion of humans-with-media, transactional distance and the role of interaction and collaboration in distance learning. Grounded Theory is used to analyze the data, which was produced from four sources: observation in virtual learning environments, interviews, educational projects and researcher's notes. Results show that two roles are evident (each treated as an analytic category): DT as promoting communication range and DT in building digital learning materials. Four properties of the first category were explored: content, agents, temporality and evaluation. For the second category, three properties were analyzed: content, nature and resources involved. The two categories were then integrated into one central category, which suggested that DT, the internet, and the use of VLE can turn the latter into Interactive Digital Didactic Material (IDDM) through the automatic registration of interactions. This transformation can take place via different languages, such as textual, audio-visual or multimodal. With respect to the linear algebra course, an imbalance in description mode approaches (formal, algebraic, and geometric) was noted, which stressed the need to encourage movement among them. This movement can be encouraged by the possibilities introduced by DT. The model constructed was used to identify patterns of use of technologies in the institutions as a way to validate the analysis and provoke reflections about the consistency between observed practices and institutional goals. In this...

O objetivo desta pesquisa é compreender o papel das tecnologias digitais (TD) nos processos educativos associados a disciplinas de Álgebra Linear de quatro cursos de Licenciatura em Matemática a distância vinculados à Universidade Aberta do Brasil (UAB), no contexto de seus Ambientes Virtuais de Aprendizagem (AVA). Trata-se de uma pesquisa qualitativa. Perspectivas associadas aos modos de descrição em Álgebra Linear, à noção de seres-humanos-com-mídias, à distância transacional e ao papel da interação e da colaboração na modalidade a distância fornecem sustentação teórica ao estudo e ao processo analítico. A Teoria Enraizada é utilizada para conduzir a análise de dados, que foram produzidos a partir de quatro fontes: observação em ambientes virtuais de aprendizagem, entrevistas, projetos político pedagógicos e notas da pesquisadora. Os resultados permitem inferir que há dois papéis em evidência, cada um analisado em uma das categorias, intituladas TD como promotoras de variedade comunicacional e TD na construção de materiais didáticos digitais. Da primeira categoria foram exploradas quatro propriedades: conteúdo, agentes, temporalidade e avaliação. Da segunda, três: conteúdo, natureza e recursos envolvidos. Posteriormente, as duas categorias foram integradas em uma categoria central que sugere que as TD, a internet e o uso do AVA podem transformar esse último em Material Didático Digital Interativo (MDDI) a partir do registro automático das interações. Esta transformação pode se dar via diferentes linguagens, como a textual, a audiovisual ou a multimodal. Do ponto de vista da disciplina de Álgebra Linear, notou-se um desequilíbrio em termos de abordagem dos modos de descrição (formal, algébrico e geométrico) e destacou-se a necessidade de estimular o movimento entre eles, que pode ser favorecido pelas possibilidades que se abrem com a presença das TD. O modelo construído foi...
Keywords: Algebras, Linear; Universidade Aberta do Brasil; Álgebra linear; Matemática - Estudo e ensino; Ensino a distância; Ensino superior